Incremental validity of ambulatory assessment of acute dynamic risk in predicting time to recidivism among prisoners on parole - Vasiljevic, Zoran (Psychology, crime & law, 2020)
This study investigates the incremental validity of changes in ten stress-related acute dynamic risk factors, collected through automated telephony over 30 consecutive days following parole, for predicting time to recidivism during the following year. Before release, the participants completed self-report assessment of some stable risk factors - impulsiveness and history of problematic substance use - as well as an assessment of symptoms of anxiety experienced during the weeks prior to release. Analysis of the baseline assessments showed that impulsiveness and a history of problematic substance use, but not pre-release symptoms of anxiety, were associated with recidivism during the parole year. Growth modelling using a linear mixed model was used to assess whether inmates on parole showed changes in acute dynamic risk factors during the first month following release. Individual growth model slopes and intercept were then extracted and used as covariates in a series of Cox regression analyses to test whether changes in acute dynamic risk factors could provide incremental predictive validity beyond baseline stable risk factors. Changes in five dynamic risk factors were associated with an increased risk of recidivism, of which daily drug use and daily summary score showed incremental predictive improvement beyond impulsiveness and history of problematic drug use.